Utilizing Coagulant Plants in the Development of Functional Dairy Foods and Beverages: A Mini Review - Bathmanathan, Rupbansraaj; Yasmin Amira, Che Yahya; M. M., Yusoff; Jaya Vejayan, Palliah (Science Alert, 2019)
Proteases are commonly available to the dairy industry and becoming saturated in their potential for further productivity among health-conscious people, which has driven positive attention towards plant-based coagulants. This review explored the possibility of coagulant plants as an ideal choice in the development of functional dairy foods and beverages and the benefits that come along to health. Dairy products like cheese require coagulation of milk by using enzymes such as rennet either in its original state, purified or genetically modified. Animal and microbe sourced coagulants have been facing many challenges due to increasing public awareness. Plant proteases are not new and have been identified previously to have the ability to coagulate milk but plants are less explored and understood in their potentials in being a milk coagulant and fortifying the curd with useful biological activities. Currently, people are looking for functional foods that provide various health benefits when consumed rather than calorie-rich food, which causes diseases. In recent times many plants are able to coagulate milk. These particular plants have been identified as an ideal choice in the development of functional dairy foods and beverages due to their dual ability of first coagulating the milk and then fortifying the curd with biologically useful compounds.